Perbedaan Persepsi Wisatawan Perempuan dan Laki-laki Mancanegara terhadap Keselamatan dan Keamanan Wisata di Kota Yogyakarta - Junanto Junanto (Program Studi Pariwisata Fakultas Ilmu Budaya Universitas Gadjah Mada Yogyakarta, 2019)
Tourism safety and security is one of the most important aspects of the tourism industry. Bad perception of tourism safety and security could greatly hinder the growth of tourists in a city. Gender, which is a topic highly related to tourism safety and security, has often been debated among researchers hence is a very intriguing issue to examine further. Therefore, research that analyses the safety and security of Yogyakarta city from the perspective of gender is extremely valuable and important. This research uses a quantitative descriptive method with a total of 102 respondents to figure out their perception toward tourism safety and security in Yogyakarta City. The quota sampling method is used to obtain a balanced proportion of male and female respondents in this research. The result shows that foreign tourists perceive Yogyakarta City as “Safe” in tourism safety and security. However, out of four dimensions that are used in this research, one dimension that discusses traffic safety in Yogyakarta has been perceived as “Unsafe” by foreign tourists. From the gender perspective, data shows that male foreign tourists perceived Yogyakarta as a safer tourist destination than female foreign tourists.